The correctional rehabilitation programme on recidivism among inmates: A case of Oke-Kura prison, Kwara State, Nigeria - Aliyu, Kehinde Adekunle (2018)
The apprehension for high rates of recidivism within Nigerian prisons received inadequate attention. It is pertinent to consider how best to practice correctional rehabilitation programmes. It is imperative to have a better orientation of rehabilitation for re-integration of inmate into the society. Therefore, the purpose of this study is to explore the correctional rehabilitation programme to reduced inmates recidivism in Oke-Kura Prison. The study used a mixed-method design. The study explored the correctional rehabilitation programme. The in-depth interview conducted with ten Informants, who are staffs from Oke-Kura prison, Kwara Sate, Nigeria were dominantly used meanwhile 242 inmates participated in the survey, purposive sampling procedure with the aid of questionnaires for data collection. The interview data was analyzed thematically with the coded data structure, while the quantitative findings was descriptively done by using analysis and results of Partial Least Square Structural Equation Modeling in determining the forces which shape the cause of recidivism. The results of the quantitative showed that there is a significant relationship between correctional rehabilitation programmes with the rate of inmate’s recidivism. In addition, the qualitative study found that there are issues affecting the effectiveness of correctional rehabilitation programme such as perception of prison staffs and inmates in participation in rehabilitation programmes are the main protagonists in the correctional rehabilitation programmes. The study has significantly contributed a new angles to the overall perspectives of how rehabilitation have been directly and indirectly influencing the recidivism. In addition the possible solutions have been proposed. The study concludes that structural factors (Rehabilitation cycles, Designing Programmes, Types of programmes and How to be accomplished) are the reasons for the intractable recidivism among inmates. For effective rehabilitation therefore, the study proposed a model to guide the rehabilitation pathways understanding and solution strategies